Morbidity profile and nutritional status of tribal under five children attending the phulwaris in rural Chhattisgarh - Dishani, Madonne Rufina; Kannan, Radhika; Philip, Reni; Ramesh, Naveen; Jain, Yogesh; Mohite, Anjali (International Journal Of Community Medicine And Public Health, 2019)
Background: According to UNICEF report, 19.8% children under-five years in India are wasted, 48% are stunted and 42.8% are underweight. Multisectoral initiatives by the national and state governments are yet to reduce the burden of malnutrition. Jan Swasthya Sahyog (JSS) Health Centre in Chhattisgarh, plays a vital role in improving nutritional status of tribal under- three children attending the phulwaris (or creches). Objectives of this study were to assess the nutritional status of under-five children attending the phulwaris located under Bamhni sub center and to identify the common morbidities among these children. Methods: The researchers conducted health check-up for 357 children in the 19 phulwaris of Bamhni sub center spread over 16 villages. Results: Mean age of children attending the phulwaris was found to be 29±12.5 months. Among the 357 children, 128 (35.9%) were underweight; 53 (14.8%) were severely underweight; 35 (9.8%) were wasted; 18 (5%) were severely wasted; 58 (16.2%) stunted and 16 (4.5%) severely stunted according to WHO growth charts for weight for age, weight for height and height for age respectively. Point prevalence of morbidity was 142 (39.7%), which included respiratory tract infection (24.6%); scabies (8.4%); otitis media (3.1%); pyoderma (2.2%); developmental delay (2.2%); worm infestation (2.2%); sickle cell anemia (0.6%) and (0.3%) had epilepsy. Conclusions: Under nutrition was still prevalent among the children attending the phulwaris and upper respiratory tract infection was the most common morbidity.